2009
DOI: 10.1149/1.3112648
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching Properties of YVO4:Eu3+ Nanophosphors Synthesized by Hydrothermal Treatment

Abstract: When YVO4:Eu3+ nanophosphors synthesized by a low-temperature wet chemical process in the presence of citrate ions are continuously excited by UV light, the photoluminescence (PL) intensity gradually decreases. This photobleaching is accompanied with the reduction of V5+ to V4+, as confirmed by electron paramagnetic resonance spectroscopy. Hydrothermal treatment of YVO4:Eu3+ nanophosphors in the presence of PO4 3- ions produces Y(V,P)O4:Eu3+ through the partial replacement between VO4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This mechanism is almost similar to the photobleaching behavior of Y͑P,V͒O 4 :Eu 3+ nanoparticles under the 302 nm excitation corresponding to O 2− -V 5+ CT, as described in our previous work. 33 The photobleaching mechanism for the 466 nm irradiation is not yet clear. Recently, Mialon et al reported that the YVO 4 :Eu 3+ nanophosphor prepared by the wet chemical precipitation shows a characteristic photobleaching behavior under the irradiation of a 466 nm laser with a power of 14 kW cm −2 and suppression of the photobleach by annealing at 1000°C in the presence of a silica matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is almost similar to the photobleaching behavior of Y͑P,V͒O 4 :Eu 3+ nanoparticles under the 302 nm excitation corresponding to O 2− -V 5+ CT, as described in our previous work. 33 The photobleaching mechanism for the 466 nm irradiation is not yet clear. Recently, Mialon et al reported that the YVO 4 :Eu 3+ nanophosphor prepared by the wet chemical precipitation shows a characteristic photobleaching behavior under the irradiation of a 466 nm laser with a power of 14 kW cm −2 and suppression of the photobleach by annealing at 1000°C in the presence of a silica matrix.…”
Section: Resultsmentioning
confidence: 99%
“…When we prepared YVO 4 :Eu 3+ nanophosphors by wet chemical precipitation in the presence of citrate ions after Huignard et al, they showed the photobleaching behavior under the irradiation of 302 nm UV light. 33 We attributed this photobleaching to the reduction of V 5+ to V 4+ combined with the formation of oxygen vacancy, which is observed by electron spin resonance ͑ESR͒ spectroscopy.…”
mentioning
confidence: 82%
“…39 For instance, Eu 3+ -doped REVO 4 aqueous colloids show a decrease in luminescence under UV excitation due to the reduction of the host matrix (V 5+ /V 4+ ) or the reduction of the activator ion (Eu 3+ /Eu 2+ ). 40,41 A reversible photoreduction of Eu 3+ upon direct Eu 3+ excitation or a reversible chemical reduction of GdVO 4 :Eu 3+ particles was observed and exploited by us to implement reactive oxygen species-sensitive nanosensors. 14,42,43 Moreover, the luminescence of Tb 3+ in YVO 4 also decreases under UV irradiation due to the partial oxidation of vacancies in air.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…Despite the common comparison with the photobleaching of organic fluorophores to affirm that lanthanide emissions are stable toward UV irradiation, the complex redox and defect chemistry of some oxide nanoparticles together with interactions with the solvent may also cause progressive time-dependent quenching of Ln 3+ emissions . For instance, Eu 3+ -doped REVO 4 aqueous colloids show a decrease in luminescence under UV excitation due to the reduction of the host matrix (V 5+ /V 4+ ) or the reduction of the activator ion (Eu 3+ /Eu 2+ ). , A reversible photoreduction of Eu 3+ upon direct Eu 3+ excitation or a reversible chemical reduction of GdVO 4 :Eu 3+ particles was observed and exploited by us to implement reactive oxygen species-sensitive nanosensors. ,, Moreover, the luminescence of Tb 3+ in YVO 4 also decreases under UV irradiation due to the partial oxidation of vacancies in air …”
mentioning
confidence: 99%
“…Besides, it is worth mentioning that as-prepared samples feature a certain lack of stability due to V 5+ to V 4+ reduction upon photoexcitation with ultraviolet light since such reduction leads to the formation of oxygen vacancies that act as quenchers of the emission. 27 Thermal processing yields higher values of the PLQY. In particular, we measure 67% for samples annealed in the conventional oven and 82% using RTA, which indicates that slow annealing at such high temperatures induces structural changes that are detrimental for the emission.…”
mentioning
confidence: 99%